Kinetics of dose-response relationship of heavy metals with dehydrogenase activity in wastewater bacteria - CO, Nweke; GC, Okpokwasili (Journal of Research in Biology, 2012)
Toxicity of Zn2+, Cd2+ and Co2+ to Escherichia coli, Pseudomonas and Bacillus species isolated from petroleum refinery effluent was assessed using dehydrogenase activity (DHA) inhibition test. Exposure of the cells to the metal ions resulted in inhibition of dehydrogenase activity. The median inhibitory concentration of the metal ions ranged from 0.0554 to 0.3883 mM (Zn2+), 0.0279 to 0.3004 mM (Cd2+) and 0.0013 to 0.2778 mM (Co2+). The trends of the inhibitory effects could be mathematically described with logistic and sigmoid dose-response models and in a manner similar to the non-competitive inhibition of enzymes. The threshold concentration above which toxic effect is observed ranged from 0.0013 mM (Zn2+ against Pseudomonas sp. RWW2) to 0.05 mM (Zn2+ against Escherichia coli). In terms of non-competitive inhibition of dehydrogenase activity, the threshold concentration ranged from 0.0183 mM (Cd2+ against Pseudomonas sp. DAF1) to 0.05 mM (Zn2+ against Escherichia coli). The coefficients of inhibition Ki correlated with the IC50, thus they are suitable parameters for kinetic analyses of metal toxicity against bacteria.